The Effect Of The Use Of Computer Helpful Learning Media On The Results Of Learning Themes Of Events In Living Class V SD - Sumilat, J M (Universitas Negeri Manado, 2019)
The purpose of this research is to know the effect of the use of computer assisted learning media on the learning outcomes of event themes in the lives of Class V elementary school students. This study uses an experimental method with bound variables (Y) is the result of learning the theme of events in the lives of students of class V SD, and the independent variable (X) is the use of computer-assisted learning media. The research was conducted at SD Negeri 2 Tataaran in October 2018. Learning outcomes data were analyzed using the t test, but previously tested normality and homogeneity as a prerequisite test. The results of this study conclude that there is an influence of the use of computer assisted learning media on learning outcomes of students in Class V SD which causes differences in achievement of learning outcomes, where the results of the theme